The Effect of Social Support and Self-Efficacy on Burnout in Working Students - Enjang Maulana; Arif Rahman Hakim; Mohammad Iqbal (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to determine the effect of social support and self-efficacy on burnout in working students. This study uses a quantitative approach with a causal associative method. The population in this study were working students with a sample of 227 respondents obtained using the Convenience Sampling technique. The data analysis technique used multiple linear regression analysis with the help of SPSS version 25.0. The results showed that social support has a significant negative effect on burnout with a significance value of 0.000 (p < 0.05). Self-efficacy also has a significant negative effect on burnout with a significance value of 0.002 (p < 0.05). Simultaneously, social support and self-efficacy have a significant effect on burnout with a significance value of 0.000 (p < 0.05). The results of the coefficient of determination test showed an R Square value of 0.177, which means that social support and self-efficacy contributed 17.7% to burnout in working students, while the remaining 82.3% was influenced by other factors outside this study. This study shows that social support and self-efficacy can help reduce burnout levels in working students.